PLASTIC WASTE, WOOD WASTE, ECONOMICALLY VALUABLE PRODUCTS - Salmawati, Salmawati; Rahman, Adiputra (Jurnal Abdi Negeriku, 2024)
This community service program aims to develop creative products with economic value from processed plastic waste and wood waste by students in the school environment. This initiative was implemented to overcome environmental problems due to the increase in plastic waste and wood waste as well as to hone students' skills and creativity in the field of handicrafts. This activity involves collecting, sorting and processing plastic and wood waste available around the school. Plastic waste is transformed into various products, namely various models of decorative flowers and plant pots, while wood waste is processed into functional items such as pen racks and aesthetic baskets. Product evaluation is carried out to ensure quality and market appeal. The results of this activity show that students are able to produce quality products that have marketability for consumers. This program not only provides economic benefits for schools and students, but also increases environmental awareness, waste management skills and student creativity. Apart from that, this program succeeded in fostering a sense of social responsibility and concern for the environment among students. Thus, this community service activity in the school environment succeeded in utilizing plastic and wood waste into creative products with economic value, supporting waste reduction efforts, and making a real contribution to sustainable education that focuses on practical skills and environmental awareness.